2010
DOI: 10.2147/ijn.s15493
|View full text |Cite
|
Sign up to set email alerts
|

Pegylation of poly(γ-benzyl-L-glutamate) nanoparticles is efficient for avoiding mononuclear phagocyte system capture in rats

Abstract: Poly(γ-benzyl-L-glutamate) (PBLG) derivatives are synthetic polypeptides for preparing nanoparticles with well controlled surface properties. The aim of this paper was to investigate the biodistribution of pegylated PBLG in rats. For this purpose, nanoparticles were prepared by a nanoprecipitation method using mixtures of different PBLG derivates, including a pegylated derivate to avoid mononuclear phagocyte system uptake. The morphology, size distribution, and surface charge of the nanoparticles were investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 42 publications
(45 reference statements)
4
24
0
Order By: Relevance
“…One approach in overcoming this problem is to increase the hydrophilicity of the particle surface. The presence of hydrophilic polymer on the surface can protect nanoparticles from capture by macrophages [5,6] . Hydrophilic polymer on the surface also improves cytoplasmic transfer of particles, [7] and reduces enzymatic degradation [8] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One approach in overcoming this problem is to increase the hydrophilicity of the particle surface. The presence of hydrophilic polymer on the surface can protect nanoparticles from capture by macrophages [5,6] . Hydrophilic polymer on the surface also improves cytoplasmic transfer of particles, [7] and reduces enzymatic degradation [8] .…”
Section: Introductionmentioning
confidence: 99%
“…The presence of hydrophilic polymer on the surface can protect nanoparticles from capture by macrophages. [5,6] Hydrophilic polymer on the surface also improves cytoplasmic transfer of particles, [7] and reduces enzymatic degradation. [8] Recent reports demonstrate that the rapid RES uptake of PLGA nanoparticles could be significantly reduced by modifying their surface with polyethylene glycol (PEG).…”
Section: Introductionmentioning
confidence: 99%
“…According to the previous work, the effective FITC concentration for in vivo imaging studies of NPs in tissues was found as 20 wt % 40. The in vivo binding of the prepared NP formulations at this ratio to bone was shown in Figure 7.…”
Section: Resultsmentioning
confidence: 63%
“…PBLG, a synthetic polypeptide, is particularly interesting because its ability to form secondary structures such as α‐helices or β‐strands, which has been shown to be important to drive NPs formation . Moreover, PBLG is a biocompatible polymer easy to modify with various chemical moieties . PEO, also often referred as poly(ethylene glycol) (PEG), is often preferred as the hydrophilic segment by virtue of its biocompatibility, safety, non‐immunogenic and non‐antigenic properties, high solubility in water, and ability to escape the mononuclear phagocyte system (MPS), which prevents preliminary elimination of the NPs from the blood stream .…”
Section: Introductionmentioning
confidence: 99%